The visualisation of fingermarks on Pangolin scales using gelatine lifters. (August 2020) - Moorat, G.; Reed, J.; Bleay, S.; Amaral, M.A.; Chappell, B.; Pamment, N.; Plowman, C.; Smith, P.A.
Highlights: The first method to lift and visualise fingermarks off Pangolin scales. Important development to combat wildlife crime. Uses adapted gelatine lifters for lifting the fingermarks. socio-technical approach to understand requirement. Straightforward, inexpensive and effective method. Abstract: Recent media reports document the plight of the Pangolin and its current position as "the most trafficked mammal in the world". They are described by some as scaly anteaters as all species are covered in hard keratinous tissue in the form of overlapping scales acting as a "flexible dermal armour". It is estimated that between 2011 and 2013, 117, 000–234, 000 pangolins were slaughtered, but the seizures may only represent as little as 10% of the true volume of pangolins being illegally traded. In this paper, methods to visualise fingermarks on Pangolin scales using gelatine lifters is presented. The gelatine lifters provide an easy to use, inexpensive but effective method to help wildlife crime rangers across Africa and Asia to disrupt the trafficking. The gelatine lifting process visualised marks producing clear ridge detail on 52% of the Pangolin scales examined, with a further 30% showing the impression of a finger with limited ridge detail. The paper builds on an initial sociotechnical approach to establishing requirement, then it focuses on the methods and outcomes relating to lifting fingermarks off Pangolin scales using gelatine lifters, providing an evaluation of its use in practice.